2008
DOI: 10.1007/s10447-007-9041-x
|View full text |Cite
|
Sign up to set email alerts
|

A Counselling Framework for Caribbean Children and Families Who Have Experienced Migratory Separation and Reunion

Abstract: This paper presents research findings on childrens' responses to migratory separation and later reunion in Caribbean families and the needs of these families when parents migrate and leave their children behind. Implications of this type of separation on children, parents and surrogate caregivers are discussed. The challenges that counsellors in both the 'sending' and host countries face working with this population are also examined and suggestions made for psychosocial intervention and guidelines for counsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…middle childhood; Collins et al, 2002), as greater emphasis has been placed on in-school adolescent populations (Lipps et al, 2010; Lowe et al, 2004, 2009; Maharaj et al, 2008). Some known predictors of depression and anxiety among Caribbean youth are parenting styles (Lipps et al, 2012; Lowe et al, 2009), domestic abuse and violence (Maharaj et al, 2008), parental migration (Pottinger & Brown, 2006) and academic tracking (Lipps et al, 2010). In addition, family environment and parenting practices (Marshall & Jackman, 2015; Marshall et al, 2014; Stubbs & Maynard, 2017) have been found to be predictors of students’ school engagement.…”
Section: Introductionmentioning
confidence: 99%
“…middle childhood; Collins et al, 2002), as greater emphasis has been placed on in-school adolescent populations (Lipps et al, 2010; Lowe et al, 2004, 2009; Maharaj et al, 2008). Some known predictors of depression and anxiety among Caribbean youth are parenting styles (Lipps et al, 2012; Lowe et al, 2009), domestic abuse and violence (Maharaj et al, 2008), parental migration (Pottinger & Brown, 2006) and academic tracking (Lipps et al, 2010). In addition, family environment and parenting practices (Marshall & Jackman, 2015; Marshall et al, 2014; Stubbs & Maynard, 2017) have been found to be predictors of students’ school engagement.…”
Section: Introductionmentioning
confidence: 99%
“…the reunion between parents and children after periods of separation. Second, they often consider children as vulnerable victims of migration (Pottinger et al, 2008), passive or invisible agents, who depend on the decisions of their parents (Bailey and Boyle, 2004; Levy et al, 2008). Although a growing body of research has underlined the role of children as active agents in family relations and in their social world (Corsaro, 1997; Ni Laoire et al, 2011), studies on transnational families have not be able to adequately deal with the participation of children in transnational migration (Dreby, 2007) and continue to consider that family migration processes depend on adults’ decisions and actions.…”
Section: From Transnational Families To Reunited Familiesmentioning
confidence: 99%
“…Family reunifi cations have been of a certain interest to clinical or therapeutic studies, which have emphasised the negative impact of separations on the "new" family and social life in the host country (Adams 2000;Artico 2003;Bernhard et al 2009;Falicov 2007;Landolt et al 2005;Pottinger et al 2008;Suarez-Orozco et al 2005). Migrating children are forced to detach themselves from a more or less extensive and meaningful system of affective relations comprising kin, neighbours and peer groups.…”
Section: Remaking Intergenerational Relationships Abroadmentioning
confidence: 99%